Grebeg Sudiro dan Representasi Keberagaman di Sudiroprajan, Kota Surakarta - Latifa Dinar Rahmani Hakim (Indonesian Journal of Religion and Society, 2020)
Several studies stated the role of government is one of the keys that influence success in overcoming diversity in a plural society. Through the case study in Sudiroprajan village, this study aims to explain the success of overcoming the problem of diversity not only because of the role of the government, but through community involvement. Using a qualitative approach, the results of this study show that the Sudiroprajan community collective awareness is an effective way to overcome the problem of diversity that has the potential to cause conflict. Collective awareness is built through socio-economic similarity, historical experience, needs and acceptance, interaction and negotiation. The building of collective awareness in the Sudiroprajan community is able to produce diversity products in the form of the Grebeg Sudiro tradition. The Grebeg Sudiro tradition has become a symbol of the Sudiroprajan village diversity as well as a medium of diversity for people outside the village.